Investigation on Dynamic Behaviors of Ship Propulsion Shafting with Misalignment Based on Stochastic Uncertainty Models - Pengfei Xing; Feng Zhao; Xiaoliang He; Guobin Li (Journal of Marine Science and Engineering)
To investigate the effect of stochastic uncertainty on the dynamic behaviors of ship propulsion shafting with misalignment, a stochastic uncertainty model of ship shafting is established based on nonparametric theory and stochastic excitation. Numerical simulation and experimental verification of the dynamic behaviors are carried out using a ship shafting test bench. The results indicate that stochastic uncertainty has a significant effect on the dynamic behaviors of shafting with misalignment. With an increase in stochastic uncertainty, the fractional frequency appears in the spectrum, and the axis trajectory becomes more complex and gradually deviates from the center orbit. Therefore, to ensure the safe navigation of ships, it is necessary to consider the stochastic uncertainty in dynamic research on the misalignment of shafting.